2022
DOI: 10.1155/2022/6181448
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Silver Nanoparticles Stabilized by Poly (Vinyl Pyrrolidone) with Potential Anticancer Activity towards Prostate Cancer

Abstract: Tumor necrosis factor (TNF-α) and inflammatory cytokine (IL-6) play a vital role in various cellular incidents such as the proliferation and death of cells during carcinogenesis. Hence, regulation of these biomarkers could be a promising tool for controlling tumor progression using nanoformulations. Silver nanoparticles-poly (vinyl pyrrolidone) (AgNPs-PVP) were prepared using the reduction of silver nitrate and stabilized with PVP. They are characterized through yield percentage, UV-VIS, FT-IR, size, charge, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 75 publications
0
10
0
Order By: Relevance
“…The results demonstrated a dose‐dependent cytotoxicity activity of AgNPs against the HepG2 cancer cell line, with a significant decrease in cell viability observed for the 20 ppm (Figure 4). Numerous in vitro studies have revealed the efficacy of biosynthesized AgNPs against a wide range of cancer cell lines, including breast (El‐Naggar et al, 2017), lung (Pucelik et al, 2022), prostate (Abdellatif et al, 2022), colon (Zein et al, 2020), and leukemia (Guo et al, 2014). Further studies and advancements in this field will find the way forward toward the biosynthesis of AgNPs and their use as cytotoxic or therapeutic agents for cancer treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results demonstrated a dose‐dependent cytotoxicity activity of AgNPs against the HepG2 cancer cell line, with a significant decrease in cell viability observed for the 20 ppm (Figure 4). Numerous in vitro studies have revealed the efficacy of biosynthesized AgNPs against a wide range of cancer cell lines, including breast (El‐Naggar et al, 2017), lung (Pucelik et al, 2022), prostate (Abdellatif et al, 2022), colon (Zein et al, 2020), and leukemia (Guo et al, 2014). Further studies and advancements in this field will find the way forward toward the biosynthesis of AgNPs and their use as cytotoxic or therapeutic agents for cancer treatment.…”
Section: Resultsmentioning
confidence: 99%
“…The results demonstrated a dose-dependent cytotoxicity activity of AgNPs against the HepG2 cancer cell line, with a significant decrease in cell viability observed for the 20 ppm (Figure 4). Numerous in vitro studies have revealed the efficacy of biosynthesized AgNPs against a wide range of cancer cell lines, including breast (El-Naggar et al, 2017), lung (Puceliket al, 2022), prostate(Abdellatif et al, 2022), colon(Zein et al, 2020),…”
mentioning
confidence: 99%
“…Other studies indicated that due to their small size, nanoparticles could enter the cell wall of bacteria and damage organelles, which results in cell death [9,10]. In contrast to their organic counterparts, inorganic antibiotics have multiple targets [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%